Mechanical Ventilation in Sepsis: A Reappraisal. (January 2017) - Zampieri, Fernando G.; Mazza, Bruno
Abstract : ABSTRACT: Sepsis is the main cause of close to 70% of all cases of acute respiratory distress syndromes (ARDS). In addition, sepsis increases susceptibility to ventilator-induced lung injury. Therefore, the development of a ventilatory strategy that can achieve adequate oxygenation without injuring the lungs is highly sought after for patients with acute infection and represents an important therapeutic window to improve patient care. Suboptimal ventilatory settings cannot only harm the lung, but may also contribute to the cascade of organ failure in sepsis due to organ crosstalk. Despite the prominent role of sepsis as a cause for lung injury, most of the studies that addressed mechanical ventilation strategies in ARDS did not specifically assess sepsis-related ARDS patients. Consequently, most of the recommendations regarding mechanical ventilation in sepsis patients are derived from ARDS trials that included multiple clinical diagnoses. While there have been important improvements in general ventilatory management that should apply to all critically ill patients, sepsis-related lung injury might still have particularities that could influence bedside management. After revisiting the interplay between sepsis and ventilation-induced lung injury, this review will reappraise the evidence for the major components of the lung protective ventilation strategy, emphasizing the particularities of sepsis-related acute lung injury.